2022
DOI: 10.1002/brb3.2501
|View full text |Cite
|
Sign up to set email alerts
|

Does social distancing affect the processing of brand logos?

Abstract: Social distancing and isolation have been imposed to contrast the spread of COVID‐19. The present study investigates whether social distancing affects our cognitive system, in particular the processing of different types of brand logos in different moments of the pandemic spread in Italy. In a size discrimination task, six different logos belonging to three categories (letters, symbols, and social images) were presented in their original format and spaced. Two samples of participants were tested: one just afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Previous research has extensively investigated attentional processing, showing that both spatial information and social factors are automatically encoded and affect the recognition of perceptual stimuli. However, a growing body of evidence has shown that standard attentional processes could be modulated by the current task and by context-relevant information (e.g., D’Ascenzo et al, 2022 ; for a discussion, see Lebois et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has extensively investigated attentional processing, showing that both spatial information and social factors are automatically encoded and affect the recognition of perceptual stimuli. However, a growing body of evidence has shown that standard attentional processes could be modulated by the current task and by context-relevant information (e.g., D’Ascenzo et al, 2022 ; for a discussion, see Lebois et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is here shown that spontaneous categorization processes are triggered, grouping individuals as a function of their mask-related behaviors. The implementation of preventive behaviors has become an integral part of people's daily lives, and much has already been done to highlight the possible effects on socio-cognitive processes 9,[52][53][54][55][56][57] . Although there is a widespread hope that we could soon overcome the Covid-19 pandemic, there is still uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors found that spaced logos were processed slower by consumers due to their unfamiliarity. Moreover, D’Ascenzo et al. (2022) found that although social distancing behavior has altered our perception towards the spaced shape of a logo, this alternative presentation can induce negative images in consumers which eventually raises a resistance in processing the stimuli.…”
Section: Theoretical Backgroundmentioning
confidence: 99%